2022
DOI: 10.1186/s12879-022-07145-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise training on symptoms of depression, physical activity level and social participation in people living with HIV/AIDS: a systematic review and meta-analysis

Abstract: Background Symptoms of depression are prevalent in people living with human immune deficiency virus/acquired immune deficiency syndrome (PLWHA), and worsened by lack of physical activity/exercises, leading to restriction in social participation/functioning. This raises the question: what is the extent to which physical exercise training affected, symptoms of depression, physical activity level (PAL) and social participation in PLWHA compared to other forms of intervention, usual care, or no tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
0
8
1
Order By: Relevance
“…[31][32][33] Consequently, HIV infection inevitably lowers the QoL due to a lack of physical activity. [34] The high-activity group was statistically higher than the other groups in psychological well-being and environmental satisfaction among the sub-variables of QoL in our study. These results suggest that individuals with a high level of physical activity increase their mental self-esteem by participating in various social and physical activities; hence, social interaction is carried out smoothly, and stress factors, such as anxiety and depression, are effectively managed.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…[31][32][33] Consequently, HIV infection inevitably lowers the QoL due to a lack of physical activity. [34] The high-activity group was statistically higher than the other groups in psychological well-being and environmental satisfaction among the sub-variables of QoL in our study. These results suggest that individuals with a high level of physical activity increase their mental self-esteem by participating in various social and physical activities; hence, social interaction is carried out smoothly, and stress factors, such as anxiety and depression, are effectively managed.…”
Section: Discussioncontrasting
confidence: 49%
“…[36][37][38] Additionally, it positively affects the physical and mental health of people with HIV. [32,34,[39][40][41] From a physiological perspective, regular physical activity stimulates the parasympathetic nervous system activity, reduces due to anxiety, and ultimately controls anxiety symptoms. [42] Overall, the regular physical activity of people with HIV can prevent anxiety and depression and helps manage stress.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in physical activity is bene cial to PLWH as physical activity has been shown to impart positive health bene ts such as improved endurance, strength, and vitality, reduced blood pressure and depressive symptoms, and an overall improvement in quality of life and function [7,4]. The physiological health bene ts of physical activity are evident in conditions such as obesity, in which regular PA causes a reduction in fat mass [8]; in sarcopenia, where regular PA improves muscle mass and function [9]; and in osteoporosis, where regular PA improves bone health, thus reducing frailty, the risk of falls and predisposition to fracture [10]. Furthermore, studies conducted on mental health, cognition and memory have reported that there is an increase in blood ow to the brain and promotion of neurogenesis when individuals engage in exercise [11], thus supporting the theory that physical exercise is bene cial to both body and mind.…”
Section: Introductionmentioning
confidence: 99%
“…Leah H et al have conducted a comprehensive review of the link between depression and cognition among PLWH ( Rubin and Maki, 2019 ). Others have reviewed depression in women living with HIV ( Fauk et al, 2022 ), men who have sex with men (MSM; Nouri et al, 2022 ; Operario et al, 2022 ), and interventions for improving depression in HIV patients ( Ibeneme et al, 2022 ), etc. However, these conventional review papers only focus on subdomains and analyze limited relevant literature.…”
Section: Introductionmentioning
confidence: 99%